Influence of Drying, Pressing, and Antioxidants on Yield and Oxidative Stability of Cold Pressed Oils - Tihomir Moslavac; Stela Jokić; Drago Šubarić; Marta Ostojčić; Srećko Tomas; Mario Kovač; Sandra Budžaki (Kemija u Industriji, 2023)
Investigated were the influence of drying and pressing parameters of rapeseed, sunflower, and safflower seeds on oil yield, as well as antioxidant addition on the oxidative stability of cold pressed oils. The parameters of the oilseeds and cold pressed oils quality (moisture content, iodine value, saponification value, peroxide value, free fatty acids, and insoluble impurities content) were determined using standard methods. In terms of oxidative stability, rosemary, green tea, and pomegranate extracts were used as natural antioxidants, and propyl gallate was used as synthetic antioxidant. The results showed that the moisture content of the oilseeds, as well as nozzle size and electromotor frequency of the press had an effect on the yield of cold pressed oil. By reducing the nozzle size and electromotor frequency, the volume of produced cold pressed oil increased. Rosemary extract effectively increased the oxidative stability of sunflower and safflower oils, and green tea extract increased the stability of rapeseed oil. Greater stabilisation of the tested oils was achieved with the addition of 0.4% of natural antioxidants compared to the addition of 0.2 %. The synthetic antioxidant, propyl gallate, failed to stabilise safflower oil, and unlike the natural antioxidants, it was less protective for rapeseed and sunflower oil.